The Meaning of Text Visualization in Contemporary Paintings in West Sumatra - Fitryona, Nessya; Sari, Dwi Mutia; Khairi, Asra Ilal; Firza, Firza (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2024)
Within two decades in West Sumatra, some artists' paintings contain visualization of letters, numbers, sentences, which are sometimes arranged scattered, even upside down. This is unusual considering that contemporary painting has developed into more sophisticated forms. This research aims to explore the meaning of text visualization in contemporary paintings of artists in West Sumatra. This research uses descriptive qualitative method with Hans-Georg Gadamer's hermeneutic approach. The object of study was selected based on purpose sampling, namely the paintings of Syahrial, Yasrul Sami, Yon Indra and Dika Adrian. The results showed that the meaning of Syahrial's painting text hints at a critical mindset in viewing the reality of life facing the value conventions of Western theories that give distance to the mindset of the community towards culture. The meaning of the text in Yasrul Sami's painting is a representation of the inner and psychological self over the problems of life. The meaning of Yon Indra's painting text leads to the essence of the attitude and mindset of the younger generation. The meaning of the text of Dika Adrian's paintings, leads to cultural consumption, social context and environment of today's young generation. From the results of the research, it can be concluded that the text in the paintings has personal meaning and social meaning. The difference in the way the text visualization is expressed in the work has an influence on cross-generational cultural consumption.